Manufaktur Sendok Makan SS304 Ukuran 180x42x1,5 mm, Cekungan 10 mm, Kapasitas 200 Biji/Jam - Wildhan Helmi Nurhuda; Syamsul Hadi; Irwansyah Setiawan; Sovyan Bagus Rahmadhana; Syienda Zahwa Saputra (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2026)
Various viruses due to unhygienic spoon surfaces, especially those that are frequently used and repeated, if they do not meet health standards in mass washing have the potential to cause disease in subsequent users as a problem faced. The manufacturing objective is to obtain a tablespoon from stainless steel, SS304 measuring 180x42x1.5 mm, a concave depth of 10 mm, and a concave length of 55 mm. Manufacturing methods include: tablespoon design; selection of SS304 raw materials, 1.5 mm thick; cutting an oval spoon shape with a total length of 180 mm, for a concave length of 55 mm, a concave width of 42 mm, a handle width of 15 mm; curving the concave (deep drawing) to obtain a concave depth of 10 mm; engraving/stamping; punching a 3 mm diameter hole at the base of the spoon at a distance of 10 mm from the tip; chamfering on 2 sides of the hole; smoothing (finishing-polishing) on all edges of the spoon; quality and dimension inspection. The manufacturing results are in the form of stainless steel spoons made of SS304 measuring 180x42x1.5 mm, a concave depth of 10 mm, and a concave length of 55 mm, a handle width of 15 mm with a production cost of IDR 16,000/unit, and a process duration of 18 seconds/unit which implies that the spoon can be used to eat solid or soupy foods which afterward must be washed clean again and can be used repeatedly.